2020
DOI: 10.3390/agronomy10071049
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Effective Microorganisms (EM) Application on the Physical Condition of Haplic Luvisol

Abstract: The study set out to determine changes in the soil air-water properties, the water-stable aggregate share and organic carbon content as effects of a five-year application of effective microorganisms (EM-A). The hypothesis that long-term applied EM-A biopreparations have a positive effect on the soil physical condition has not been confirmed. Haplic Luvisols originating from silt were studied in a field experiment after EM-A biopreparation treatment. The soil samples with the natural structure preserved intact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…Therefore, an important element in management of soils is to prevent their degradation. Taking preventive actions is considered to be a better approach than the subsequent implementation of soil remediation measures [5][6][7][8][9]. Soil is an irreplaceable element of the environment and it is subjected to the pressure of various degrading factors.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an important element in management of soils is to prevent their degradation. Taking preventive actions is considered to be a better approach than the subsequent implementation of soil remediation measures [5][6][7][8][9]. Soil is an irreplaceable element of the environment and it is subjected to the pressure of various degrading factors.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Szymanek et al [82] reported a negative impact of EM on the amount of available forms of soil phosphorus, potassium, and magnesium. Likewise, long-term studies by Pranagal et al [71] did not confirm the positive effect of EM on the physical properties of the soil, and the application of the preparation led to a decrease in the content of organic carbon in the soil. In our research, a moderate effect of the EM preparation on the content of OC, TN, P, Mg, and TMN in the soil was observed, although, usually, the values of these parameters were higher in the variants including their application.…”
Section: Discussionmentioning
confidence: 87%
“…Even though the number of scientific publications on the impact of EM on the physical and chemical properties of soil is relatively high, there are just a few studies on the effect of their use on soil microorganisms. Pranagal et al [71] suggest the prudent use of this type of product due to the risk of disturbance in the functioning of the soil environment as a result of the introduction of foreign microorganisms and their ability to decompose soil organic matter. Other authors [26], however, negate the possible permanent effects of EM on the composition and activity of indigenous soil microorganisms, assuming the short-term nature of possible changes in their numbers.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements carried out in the third decade of June showed a decrease in aeration porosity in all variants compared to the measurements carried out in May. Researchers investigating effective microorganisms found no significant effect on porosity (Pranagal et al, 2020). At the end of July, aeration porosity ranged from 33.76% to 43.29%.…”
Section: Soil Aeration Porositymentioning
confidence: 79%